Development of Induction Logging Technology for Non-Stationary Conditions While Drilling Subhorozontal Sections of Oil and Gas Wells - V. K. Teplukhin; A. N. Ratushnyak; V. I. Kostitsyn; Сяолун Ван (Vestnik Permskogo Universiteta: Seriâ Geologiâ, 2017)
The article presents the results of development of the induction logging module designed for resistivity measurements while drilling horizontal and directional wells for oil and gas. Materials of the tool testing during the drilling of wells in the oil field in the Republic of Bashkortostan are shown. We introduce the comparative analysis of resistivity data obtained after completion of the drilling, and the results obtained with developed complex as part of the LWD telemetry system TARGET during the drilling. The technical characteristics of complex MIR are presented.